Biological Control of Coleopteran Pests - Purti,; Rinku,; Jaglan, R. S.; Rolania, Krishna (International Journal of Bio-resource and Stress Management, 2023)
Coleopteran pests having the modified forewings which serves as protective covers for the membranous hind wings and commonly called as beetle. Most of them are important pest of agriculture, forestry, fruit trees and stored grain while only a few species are considered to be beneficial. Man has probably been plagued by insect pests ever since he began to grow crops and rear animals. Worsened by the ability of these pests to emerge and re-emerge, man, his crops, livestock as well as his socio-economic status stand on the threshold of destruction. Challenged by this danger and frustrated by the demerits of chemical pest control, man began to explore the use of identified natural enemies as agents of bio control to manage potentially damaging population below levels that they can cause economic injury. Biologically we can control the coleopteran pests with the help of several predators, parasitoids and entomopathogens, ants, mites and mammals. Tree creepers, chickadees, nuthatches, flycatchers, swallows, tanagers, finches, thrushes, jays, wrens, kinglets, and warblers are the predatory birds that feed on the different species of beetles. Diabrotica sp., Solenopsis geminate and Pheidole megacephala are the predatory ants that removed 80% of exposed Diabrotica eggs. Iponemus sp., Pyemotes giganticus and Pymotes dryas are the predatory mites that are used in controlling the pine and bark beetles. Similarly, entomopathogens are also play an important role in controlling the coleopteran pests and it includes fungi, viruses, bacteria and nematodes.